Association between urinary metallothionein concentration and causes of death among cadmium-exposed residents in Japan: a 35-year follow-up study - Lianen Li; Rie Okamoto; Xian Liang Sun; Teruhiko Kido; Kazuhiro Nogawa; Yasushi Suwazono; Hideaki Nakagawa; Masaru Sakurai (Environmental Health and Preventive Medicine)
Background: As research progresses, there is a growing body of evidence indicating that urinary metallothionein (MT) levels may be elevated in individuals exposed to cadmium (Cd). This study aimed to investigate the potential association between urinary MT levels and causes of mortality among residents of the Kakehashi River Basin who have been exposed to Cd. Method: The study involved a total of 1,398 men and 1,731 women were conducted between 1981 and 1982, with follow-up until November 2016. The study employed the Cox proportional-hazards model to examine the association between higher urinary MT concentrations and the risk of all-cause or cause-specific mortality within the population. Furthermore, the Fine and Gray competing risks regression model was used to evaluate the links between specific causes of death. Results: The findings revealed that elevated urinary MT concentrations were linked to increased all-cause mortality and higher mortality rates from renal and urinary tract diseases across all participants. Specifically, in men, higher urinary MT levels were associated with elevated all-cause mortality, while in women, increased concentrations were linked to higher mortality from endocrine, nutritional, and metabolic diseases, as well as cardiovascular diseases. Even after adjusting for competing risks, higher urinary MT concentrations were associated with tumor-related mortality in men and continued to be associated with cardiovascular disease mortality in women. Conclusions: In conclusion, the results suggest that women may face a greater risk of adverse health effects due to prolonged exposure to Cd. Urinary MT levels could potentially serve as a biomarker for mortality from these diseases in populations chronically exposed to Cd.